Information security and privacy : 10th Australasian Conference, ACISP 2005, Brisbane, Australia, July 4-6, 2005 : proceedings - ACISP; Boyd, Colin; González Nieto, Juan M. (Lecture Notes in Computer Science, 2005)
This book constitutes the refereed proceedings of the 10th Australasian Conference on Information Security and Privacy, ACISP 2005, held in Brisbane, Australia in July 2005. The 45 revised full papers presented together with 3 invited papers were carefully reviewed and selected from 185 submissions. The papers are organized in topical sections on network security, cryptanalysis, group communication, elliptic curve cryptography, mobile security, side channel attacks, evaluation and biometrics, public key cryptosystems, access control, digital signatures, threshold cryptography, protocols, group signatures, credentials, and symmetric cryptography.